Heavy Metal Effects from Al-Dura Power Station on Plant Citrus Aurantium L. (Global Journal of Science Frontier Research, 2016)
Three selected sites with gradual distances from Al-Daura thermal power station (0.5 km (St.1), 1km (St.2) and 2km (St.3) were chosen for sampling according to the direction of downwind of site. In addition, one of unpolluted site for comparison as control site in Baghdad around 4 Km upwind from Al-Daura thermal power station. The samples were taken for two seasons; the first season was in December 2014 and the second season was in March 2015.The results of heavy metals in plant tissues showed a high concentration of Ni, Cd and Cu in the leaves and root of Citrus aurantium L. in all the three sites; the highest concentrations were in site 2, while the Pb concentrations in site 1 and 2 were less from that of the site 3. There was no significant difference in the concentrations of Cd and Pb between the two seasons, while there was a significant increase in the concentrations of Ni and Cu in the second season than in the first season. The chlorophyll and protein content in Citrus aurantium L. trees were higher in the control site than the other three sites. Site 2 recorded the lowest value. There were significant increases in chlorophyll and protein content in the second season than that in the first season.
Keywords: Citrus aurantium L; protein content; Al-Daura; plant tissues